Effect of Rosella (Hibiscus Sabdariffa l.) Addition on Antioxidant Activity and Acceptability of Pedada (Sonneratia Caseolaris) Slice Jam - Pangestu, Chandra Trisna; Andriyono, Sapto; Saputra, Eka (Grouper, 2025)
The Pedada fruit (Sonneratia caseolaris) is highly nutritious, containing vitamins A, B, B2, and C and phytochemicals such as flavonoids, steroids, and alkaloids. This study aims to develop Pedada fruit slice jam to enhance the practicality of conventional jam. However, the final product's unattractive color necessitates using natural colorants and bioactive compounds to enhance antioxidant activity. Roselle flower extract (Hibiscus sabdariffa L.), rich in anthocyanins with antioxidant properties, was used as a natural colorant. This research examines the effect of roselle extract on the antioxidant activity and acceptability of Pedada fruit sheet jam using a Completely Randomized Design (CRD) with four treatments: control (without roselle extract), and additions of 30% (P1), 40% (P2), and 50% (P3) roselle extract, each with five replications. Antioxidant activity, hedonic testing, and proximate analysis (carbohydrates, fats, moisture, ash, and protein) were measured. Data analysis was performed using SPSS with one-way ANOVA and Duncan's Multiple Range Test (DMRT) at a 95% significance level. The results show that adding roselle extract significantly enhances antioxidant activity, with the highest IC50 value observed at the 50% treatment (P3) at 25.380 ppm, compared to the control (P0) at 55.429 ppm. Furthermore, the addition of roselle extract improves product acceptability.